(untitled) (Research, Society and Development, 2021)
Introduction: The study aimed to analyze the scientific production related to nursing history having the photograph as a research source. Methodology: An integrative review was carried out in the gray literature and in the Virtual Health Library Portal, where eight articles were selected from the databases SCIELO, LILACS, BDENF and MEDLINE. Results: There is evidence that all articles are authored by Brazilian nurses on the theme of the Second World War, present in five of the eight articles. It should be noted that the authors are present in more than one of these five articles, especially those from Rio de Janeiro; The most frequent approach found is the socio-historical approach having one point in common, which is the articulation between photography and other sources of study, such as the use of historical documentation to ratify the context and content of the image. Conclusion: The use of photography evidenced the view that society has about nursing, as well as, made it clear that the Nursing History must be explored with new studies and members. To this end, investments must be made for historical research to use different sources, including the use of photography, as this way, there will be the use of knowledge, which is built on fundamentals and as much exploration as possible.